Proposing a non-monetary Islamic index for poverty measurement at Lembaga Zakat Selangor (LZS), Malaysia / Mohamed Saladin Abdul Rasool - Abdul Rasool, Mohamed Saladin (Institute of Graduate Studies, UiTM, 2016)
In practice, most zakat organizations in Malaysia use the monetary approach in measuring poverty through the conventional Poverty Line Income (PLI) method, and recently the had al kifayah (HAK) approach was adopted by zakat institutions. The main aim of the present study is to present a multidimensional poverty measurement from an Islamic perspective as an alternative to the current monetary measurement. The study proposes an Islamic Poverty Index (IPI) which consists of non-monetary indicators comprising of maqasid-al shariah (objective of religion) elements, namely, religion, knowledge, physical self, offspring and wealth. The respondents of this cross-sectional study were recipients of zakat aid from Selangor Zakat Board (LZS), which has the highest zakat collection in Malaysia. The two main phases involved in the study are the development of a questionnaire as the research instrument and the data collection stage. An expert review was conducted to develop the questionnaire and the data collection was carried out through a survey aided by a structured questionnaire on selected heads of poor households using the proportionate sampling method in the state of Selangor, the most populated state (with the highest number of Muslims) in Malaysia…